Two new species of the genus Apolygus China (Hemiptera: Heteroptera: Miridae: Mirinae) from the Korean Peninsula, with a key to Korean Apolygus species - Kim, Junggon; Jung, Sunghoon (Zootaxa, 2016)
Two new species of the genus Apolygus are described from the Korean Peninsula: A. rubrifasciatus sp. nov. and A. atriclavus sp. nov. Descriptions and diagnoses, and some biological information are presented with photographs and illustrations. A key to the Korean Apolygus species is also provided.